Evidence of Galactic Interaction in the Small Magellanic Cloud Probed by Gaia-selected Massive Star Candidates - Satoya Nakano; Kengo Tachihara; Mao Tamashiro (The Astrophysical Journal Supplement Series)
We present identifications and kinematic analysis of 7426 massive (≥8 M _⊙ ) stars in the Small Magellanic Cloud (SMC), using Gaia DR3 data. We used the Gaia ( G _BP − G _RP , G ) color–magnitude diagram to select the population of massive stars, and parallax to omit foreground objects. The spatial distribution of the 7426 massive star candidates is generally consistent with the spatial distribution of the interstellar medium, such as H α and H i emission. The identified massive stars show inhomogeneous distributions over the galaxy, showing several superstructures formed by massive stars with a several hundred parsec scale. The stellar superstructures defined by the surface density have opposite mean proper motions in the east and west, moving away from each other. Similarly, the mean line-of-sight velocities of the superstructures are larger to the southeast and smaller to the northwest. The different east–west properties of the superstructures’ proper-motion, line-of-sight velocity indicate that the SMC is being stretched by tidal forces and/or ram pressure from the Large Magellanic Cloud to the southeast, thereby rejecting the presence of galactic rotation in the SMC.